2022
DOI: 10.3389/fpsyg.2022.868825
|View full text |Cite
|
Sign up to set email alerts
|

Exploring L2 Engagement: A Large-Scale Survey of Secondary School Students

Abstract: Engagement, a psychological individual difference variable with three facets (vigour, dedication and absorption), has recently attracted scholarly attention. Through a large-scale survey, we examined what we call ‘L2 engagement’ among 21,370 secondary school students in China, with an L2 engagement scale adapted from the Utrecht Work Engagement Scale (UWES)-student version. Factor analysis showed this scale to be empirically unidimensional with three highly intercorrelated facets and very high internal consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…r = .1) in bivariate analyses. This criterion helps to ensure the principle of parsimony (Leech et al, 2014), which has also been adopted in some recent studies (e.g., Wang et al, 2022;Wei et al, 2022b).…”
Section: Rq2 the Influence Of The Selected Sociobiographical Variable...mentioning
confidence: 99%
See 3 more Smart Citations
“…r = .1) in bivariate analyses. This criterion helps to ensure the principle of parsimony (Leech et al, 2014), which has also been adopted in some recent studies (e.g., Wang et al, 2022;Wei et al, 2022b).…”
Section: Rq2 the Influence Of The Selected Sociobiographical Variable...mentioning
confidence: 99%
“…This study identified a 'strong' association (r s = .34, p = .04) between bilingualism (operationalised as English proficiency) and well-being. The two studies reviewed above produced relatively large effect sizes (approaching the 'very large' benchmark of .30); however, these results probably over-estimated the strength of association between bilingualism and well-being because bivariate analyses (e.g., correlation) tend to generate inflated effect sizes (Wang et al, 2022;Wei et al, 2022a). One solution to this problem is to employ multivariate analyses that will generate a more comprehensive picture in terms of effect sizes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…correlation analysis and t-test) tend to generate inflated effect sizes compared with multivariate analyses (e.g. hierarchical regression) (Wei, Reynolds, Kong, & Liu, 2022;Wang et al, 2022). Given the multivariate nature of L2 learning, multivariate analyses paint a much more accurate picture than bivariate analyses (Wei, Wang & Liu, 2022;Wang et al, 2022).…”
mentioning
confidence: 99%